Analisis Porter’s Five Force Pada Pusat Ponsel dan Laptop (PPL) di Kota Palangka Raya - Newson Renady; Natanael Wongkar; Natasya Syelomita Halim; Yosafat Dame Parlindungan; Elvira Pebiana (FKIP, Universitas Palangka Raya, 2025)
This study examines the landscape of digital device businesses in Palangka Raya by focusing on external factors that influence business sustainability. Utilizing a strategic evaluation approach based on five competitive forces, the research identifies various pressures and opportunities faced by entrepreneurs striving to maintain their presence amid a dynamic market environment. Data were collected through in-depth interviews with key stakeholders and supplemented by document analysis related to commercial activities in this sector. The findings reveal that the emergence of new entrants poses a significant challenge, primarily due to easy market access and innovative business models. Additionally, relationships with suppliers and the ability to adapt to customer needs are crucial aspects for maintaining competitive advantage. The rise of alternative products and intense competition compel businesses to continuously improve services and foster customer loyalty. This study emphasizes the importance of developing collaboration-based strategies, leveraging information technology, and enhancing customer interaction quality as key factors for survival in an evolving industry. The results are expected to serve as practical references for business practitioners and policymakers in designing adaptive measures to strengthen their position in the growing local market